2016
DOI: 10.1111/imr.12466
|View full text |Cite
|
Sign up to set email alerts
|

Properdin: a tightly regulated critical inflammatory modulator

Abstract: SummaryThe complement alternative pathway is a powerful arm of the innate immune system that enhances diverse inflammatory responses in the human host. Key to the effects of the alternative pathway is properdin, a serum glycoprotein that can both initiate and positively regulate alternative pathway activity. Properdin is produced by many different leukocyte subsets and circulates as cyclic oligomers of monomeric subunits. While the formation of non‐physiological aggregates in purified properdin preparations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 224 publications
1
85
0
Order By: Relevance
“…The alternative pathway amplifies the initial response and maintains a low level of activity through a tick-over mechanism. The alternative pathway might also have a role in initiation of the complement cascade, but the question of whether an initiating PRP acts in this pathway is not yet resolved 7,13 . In settings such as thromboinflammation, complement can be activated via non-canonical routes that bypass these three pathways, for example, by serine proteases with promiscuous enzymatic activity in the intracellular space or in the vasculature 14 .…”
Section: The Role Of Complement In Host Defencementioning
confidence: 99%
“…The alternative pathway amplifies the initial response and maintains a low level of activity through a tick-over mechanism. The alternative pathway might also have a role in initiation of the complement cascade, but the question of whether an initiating PRP acts in this pathway is not yet resolved 7,13 . In settings such as thromboinflammation, complement can be activated via non-canonical routes that bypass these three pathways, for example, by serine proteases with promiscuous enzymatic activity in the intracellular space or in the vasculature 14 .…”
Section: The Role Of Complement In Host Defencementioning
confidence: 99%
“…Such modulators typically contain pattern recognition regions and binding sites for complement components, activators, and/or regulators. For example, although properdin is best known for its ability to stabilize the C3bBb convertase, the protein has also been reported to act as an initiator that binds markers such as LPS and recruits soluble C3b (as a starter molecule) to the target surface (Figure B); however, the relevance of this bridging function is still debated . Although the molecular details remain to be elucidated, there is increasing evidence for a recruitment of C3b by P‐selectin on platelets and endothelial cells that could induce or exacerbate complement activation .…”
Section: Complement C3: a Functional Hub In Innate Immunity And Beyondmentioning
confidence: 99%
“…In the presence of intact C3, it is virtually impossible to demonstrate whether properdin acts in a recognition manner or subsequently binds to C3b. On the other hand, purified properdin is sensitive to aggregation into sticky multimers, and these aggregates, referred to as activated properdin, do not behave as the native form; thus, results with purified properdin must be judged with care (30,31), especially in unfractionated preparations (32). Early preparations of properdin, such as those used in the initial studies by Pillemer et al (1), were later shown to contain impurities and high molecular aggregates of properdin, which were lost when adsorption to zymosan was omitted from the purification protocols (30,33,34).…”
Section: Significancementioning
confidence: 99%